Estado actual de las enfermedades y otros signos de deterioro coralino en siete arrecifes del Parque Nacional Archipiélago de Los Roques, Venezuela - García, Adriana (2003)
This work was aimed to determine the incidence of coral diseases in six different reef sites at the Parque Nacional Archipiélago de Los Roques, Venezuela: Arrecife de herradura, Arrecife costanero, both at Dos Mosquises Sur Key, Boca de Cote, Carenero, Crasquí and Pelona de Rabusquí. Each reef was surveyed by using ten 10 m2 - band transects (10 x 1 m), placed parallel to the long axis of the reef within a depth gradient ranging from 1 to 9 m depth. All healthy and injured corals, along each band transect, were counted and identified to species level. Additionally, all diseases and recent mortality that were still identifiable on each colony were also recorded. The occurrence of diseased colonies and other signs of reef decline between localities were compared by means of a Chi2 test. The absolute, relative and mean incidence was estimated for each disease and other signs of damage observed for all coral species surveyed at each site. The overall incidence of coral diseases was low for all the localities surveyed, only 6.04 % of the 3 344 colonies observed, showed signs of diseases. The most important diseases recorded were the Yellow-Blotch Disease (YBD) and Dark Spots Disease (DSD) with 2.1% ± 1.52 y 2.1% ± 2.54, respectively. Significant differences were found in the incidence of coral diseases between reef sites (Chi2 p < 0.05). Finally, the occurrence of colonies injured by parrotfish bites and pomacentrids was higher compared with the incidence of coral diseases for all the reefs surveyed. In conclusion, currently the proportion of healthy colonies at Los Roques coral reefs is higher than the percentage of both diseased and injured colonies.